Meaning of life among patients diagnosed whit cancer - Huamani, Julio César (2019)
This study aimed to analyze the meaning of life among cancer patients, according to the type of cancer, stage of the disease, time of diagnosis, education level, sex and age. The sample consisted of 100 patients whose average age was 48.4 years, out of which 72% were females and 28% were males. The predominant types of cancer were breast cancer (26%), cervical cancer (23%) and stomach cancer (8%). Fifty percent (50%) of the patients were diagnosed with stage 2 cancer. The research used the Purpose in Life (PIL) test, the Argentine adaptation of which was performed by Gottfried (2016). It is concluded that medium and good levels of meaning of life prevailed among research subjects, and noogenic neurosis or depression only occurred in 15% of such population. However, patients with osteosarcoma and lung cancer, those diagnosed with stage 3.